PENGARUH LITERASI DIGITAL TERHADAP HASIL BELAJAR PAI SISWA KELAS X DI SMKN 2 BUKITTINGGI - Fitra Aini; Yulia Rahman (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Digital literacy is the ability to utilize various digital media. It influences learning outcomes by assessing the students' success level after participating in an educational activity. This study, conducted at SMKN 2 Bukittinggi, addresses issues such as moderate cognitive learning outcomes in the 10th-grade students due to an emphasis on intellectual behavior. Additionally, there's a lack of training from teachers or the school regarding digital literacy and insufficient student response to digital literacy education. The research aims to analyze digital literacy skills, Islamic Education learning outcomes, and the impact of digital literacy on student performance at SMN 2 Bukittinggi. The study follows a quantitative approach, utilizing a questionnaire as the research instrument. The informants are 10th-grade students in office management and business services classes.The research results indicate that 45% of students in the 2023/2024 academic year at SMKN2 Bukittinggi have high learning outcomes in Islamic Education. Digital literacy significantly and positively influences these outcomes, supported by a calculated T-value of 45.886 ≥ 1.66235 (table value), with a significance level of 0.000 ≤ 0.05. This rejects the null hypothesis (Ho) and accepts the alternative hypothesis (H1), meaning digital literacy has a positive and significant impact on student learning in Islamic Education at SMKN 2 Bukittinggi. Furthermore, the linear relationship between literacy and learning outcomes is confirmed by the linear test, where the obtained F-value is 0.9521 ≤ F-critical 3.96, and the significance level is 0.556 (≥ 0.05). Support for digital literacy in education can assist students in achieving better learning outcomes.